Applicability of diverging diamond interchange in the Philippines - Sy, Kyle Michael (Animo Repository, 2022)
The conventional diamond interchange may be one of the most common interchange designs in the Philippines but an increase in vehicle volumes throughout the years have challenged the design of this interchange due to heavy traffic congestion, high delays, queues, and low levels of service. The diverging diamond interchange is one of the substitutes to the conventional diamond interchange and promises an improvement in overall performance, which will be examined by the researcher. The conventional diamond interchange studied was the Karuhatan interchange in Valenzuela City wherein a traffic volume count was conducted on two Fridays during the morning and afternoon peak hours. The vehicles were also tallied based on vehicle type and the different driving behaviors were examined. The data collected as well as the observed behaviors were plugged into the VISSIM microsimulation software which is where the simulation of both conventional and diverging diamond interchanges were conducted. The simulation revealed that the diverging diamond interchange design would not be applicable in Karuhatan interchange since the proportion of left-turning vehicles, between 22% to 30%, is too low, which has resulted in lower delays and queues for the two out of four left-turning movements but higher delays and queues for the other two movements as well as the two through movements. To improve on the study, traffic signals may be optimized, and the simulation time may be increased.